2008
DOI: 10.2174/092986608785133591
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Peptides and Innate Immune Response in Mollusc

Abstract: The nervous and the immune systems can exchange information through opioid peptides. Furthermore, some opioid peptides can function as endogenous messengers of the immune system, and participate in an important part in the regulation of the various components of the immune response. Since the capacity of immunocytes to release and respond to opioid neuropeptide messengers is not restricted to mammalian organisms, recent studies have indicated that invertebrate models have been particularly useful to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Similar to cells of the vertebrate monocyte/macrophage lineage, PAMP-activated immunocytes achieve pathogen elimination essentially through chemotaxis, phagocytosis, and cytotoxic processes [30]. In the Mediterranean mussel, agranular hemocytes are cells able to divide as they show replication-dependent chromosomal damage [98] whereas the heterogeneous and abundant granulocytes can be regarded as differentiated cells, mostly phagocytic and able to release antimicrobial peptides [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to cells of the vertebrate monocyte/macrophage lineage, PAMP-activated immunocytes achieve pathogen elimination essentially through chemotaxis, phagocytosis, and cytotoxic processes [30]. In the Mediterranean mussel, agranular hemocytes are cells able to divide as they show replication-dependent chromosomal damage [98] whereas the heterogeneous and abundant granulocytes can be regarded as differentiated cells, mostly phagocytic and able to release antimicrobial peptides [41].…”
Section: Resultsmentioning
confidence: 99%
“…According to morphological observations and flow cytometry, bivalve hemocytes are heterogeneous and very dynamic cells of 7-10 μm size which can be classified into large granulocytes (eosinophilic) most active in phagocytosis and ROS production, large hyalinocytes with intermediate activity, small non-phagocytic semigranular cells (basophilic) and the less abundant blast-like hyalinocytes [26-28]. As Mytilus hemocytes respond to interleukin 1 (IL 1), tumour necrosis factor (TNF) and to opioid peptides (the endogenous messengers between the nervous and the immune system) they may be part of an ancient monokine-like network [29,30]. Also relevant to the use of mussels as biosensors of coastal pollution [31] the interdependence of cell processes modulated by chemical contaminants and infective agents requires additional study [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid peptides are well known effectors of in vivo and in vitro immune responses. Furthermore, it has been shown that the opioids have broad immunomodulatory activity, both on cellular and humoral immune responses and are able to modulate inflammatory cytokine production [9][10][11]. This immunomodulatory activity is mediated by either the µ, δ or κ opioid receptors that are expressed on immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…In gastropod molluscs endogenous opioid systems are involved in modulation of nociception and analgesic responses (Kavaliers, 1991; Liu, 2008; Miller-Pérez et al, 2008). At a behavioral level the terrestrial pulmonate Cepaea nemoralis has been shown to develop tolerance to morphine induced analgesia (Kavaliers and Hirst, 1986), but required specific environmental cues for the tolerance to be expressed, consistent with a classical conditioning of habituation model.…”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%